ANALYSIS OF SOLVATOCHROMISM OF A BIOLOGICALLY ACTIVE KETOCYANINE DYE USING DIFFERENT SOLVENT POLARITY SCALES AND ESTIMATION OF DIPOLE MOMENTS: Life Science-Physics - J. THIPPERUDRAPPA (International Journal of Life Science and Pharma Research, 2014)
The effect of solvents on photophysical properties namely absorption transition energy, fluorescence transition energy and stoke’s shift of a ketocyanine dye 2,5-di[(E)-1-(4 - aminophenyl) methylidine]-1- cyclopentanone (2,5-APMC) is analyzed using Lippert-Mataga bulk polarity function, Reichardt’s microscopic solvent polarity parameter and Kamlet’s multiple linear regression approach. The spectral properties better follow Reichardt’s microscopic solvent polarity parameter than Lippert-Mataga bulk polarity function. This indicates that both general solute – solvent interactions and specific interactions are operative. Kamlet’s multiple linear regression approach indicates that polarizability/dipolarity solvent influences are more compare to HBD and HBA solvent influences. The solvatochromic correlations are used to estimate excited state dipole moment using theoretically determined ground state dipole moment. The excited state dipole moment of dye is found to be larger than its corresponding ground state dipole moment and, ground state dipole moment and excited state dipole moments are not parallel, but makes an angle of 570 .